2019
DOI: 10.1186/s12889-019-7104-7
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use among Nigerian university students: prevalence, correlates and frequency of use

Abstract: Background: Globally, alcohol use is responsible for 320 deaths every hour, and the impact is more among those in the younger age group. Despite the adverse health and social challenges associated with alcohol use, alcohol remains the most used and abused psychoactive substance among young adults. Our study aimed at determining the prevalence, correlates and frequency of alcohol use among young adults in two Nigerian universities. We further explored the role of family structure, family support and religion/re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
44
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 46 publications
14
44
2
Order By: Relevance
“…This study has also shown that male adolescents were more addicted to alcoholic beverage than their female counterparts, which corroborates with studies in Ibadan [20], Ilorin and Nasarawa [22]. This finding is not surprising, because alcoholic beverage consumption by females is culturally unacceptable in Ibadan, in the South West and Ilorin/Nasarawa, in the north--central part of the country and, most importantly, in the environment of the current study [6,8,9].…”
Section: Key Results/interpretationsupporting
confidence: 92%
See 1 more Smart Citation
“…This study has also shown that male adolescents were more addicted to alcoholic beverage than their female counterparts, which corroborates with studies in Ibadan [20], Ilorin and Nasarawa [22]. This finding is not surprising, because alcoholic beverage consumption by females is culturally unacceptable in Ibadan, in the South West and Ilorin/Nasarawa, in the north--central part of the country and, most importantly, in the environment of the current study [6,8,9].…”
Section: Key Results/interpretationsupporting
confidence: 92%
“…The relationship between religious adherence and alcohol addiction has been considered by researchers [11,[20][21][22][23][24][25][26]. Most of these studies showed that alcohol use was inversely related to frequency of participation in religious activities.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, harmful alcohol consumption among all undergraduates was less than 5%. This proportion is quite low as compared to a level of almost 10% and over 30% among University students in Ethiopia and Nigeria respectively [26,27]. In these studies, the man reported key drivers, that could also be valid in our study, include peer pressure and some socio-economic factors.…”
Section: Discussionsupporting
confidence: 45%
“…students from Canada (21) , Chile (22) , Hungary, Lithuania, Slovakia (23) , Nigeria (24) , and Europe in general (25) .…”
Section: Discussionmentioning
confidence: 99%